A Wire Indent Profiling System for the Assessment of Bond and Splitting Propensity of Prestressing Wires Used in Pretensioned Concrete Railroad Ties - Beck, B. Terry; Robertson, Aaron A.; Peterman, Robert J.; Riding, Kyle A. (Rural Railroad Safety Center, Kansas State University., 2021)
The focus of this research was the creation of an automatic non-contact laser-based indent profiling system for the purpose of rapidly assessing geometrical characteristics of indented wires used in the manufacture of pretensioned concrete railroad ties. The process of measuring indent geometrical characteristics by traditional means is a time-consuming process which severely limits the frequency of testing and prevents statistically relevant sample sizes. In parallel with concrete prism transfer length and splitting propensity testing conducted in conjunction with this project, this system was used to identify which indent characteristics were directly related to both bond and splitting propensity in pretensioned concrete ties. This report details the automation of this indent profiling system and the results obtained for many different indented wires that were currently or historically used to manufacture pretensioned concrete railroad ties.
Keywords: Indented wire geometry; Transfer length; Cracking and splitting; Prestressed concrete; High-speed rail; Railroad ties